Delivering an evidence-based outdoor journey intervention to people with stroke: Barriers and enablers experienced by community rehabilitation teams - Middleton Sandy; McCluskey Annie (BMC, 2010)
Abstract Background Transferring knowledge from research into practice can be challenging, partly because the process involves a change in attitudes, roles and behaviour by individuals and teams. Helping teams to identify then target potential barriers may aid the knowledge transfer process. The aim of this study was to identify barriers and enablers, as perceived by allied health professionals, to delivering an evidence-based (Level 1) outdoor journey intervention for people with stroke. Methods A qualitative design and semi-structured interviews were used. Allied health professionals (n = 13) from two community rehabilitation teams were interviewed, before and after receiving feedback from a medical record audit and attending a training workshop. Interviews allowed participants to identify potential and actual barriers, as well as enablers to delivering the intervention. Qualitative data were analysed using theoretical domains described by Michie and colleagues. Results Two barriers to delivery of the intervention were the social influence of people with stroke and their family, and professionals' beliefs about their capabilities. Other barriers included professionals' knowledge and skills, their role identity, availability of resources, whether professionals remembered to provide the intervention, and how they felt about delivering the intervention. Enablers to delivering the intervention included a belief that they could deliver the intervention, a willingness to expand and share professional roles, procedures that reminded them what to do, and feeling good about helping people with stroke to participate. Conclusions This study represents one step in the quality improvement process. The interviews encouraged reflection by staff. We obtained valuable data which have been used to plan behaviour change interventions addressing identified barriers. Our methods may assist other researchers who need to design similar behaviour change interventions.